Fluorescence Imaging to Identify and Preserve Fifth Intercostal Sensory Nerves during Bilateral Nipple-sparing Mastectomies - Alberto O. Rancati, MD, PhD; Claudio Angrigiani, MD; Maurice Y. Nahabedian, MD; Agustin Rancati, MD; Kevin P. White, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2023)
Summary:. The use of nipple-sparing mastectomies has increased steadily over the past 10–15 years. However, one major source of patient dissatisfaction with both skin- and nipple-sparing mastectomies is lost skin and/or nipple sensation postoperatively due to intraoperative, iatrogenic sensory nerve injury. We summarize the case of a 41-year-old woman with BRCA(+) breast cancer who underwent bilateral, risk-reducing nipple-sparing mastectomies, immediately followed by bilateral, direct-to-implant breast reconstruction, in whom a prototype fluorescent imaging camera was used to facilitate sensory nerve identification and preservation. Preoperatively, tactile and thermal quantitative sensory testing were performed using a 30-gauge needle to determine baseline sensory function over both breasts. Then, nipple-sparing mastectomies and direct-to-implant reconstruction were performed. Using a laterally-displaced submammary approach, the anterior intercostal artery perforator neurovascular pedicle was preserved. Then a prototype camera, which emits near-ultraviolet light, was used to detect nerve autofluorescence. Intraoperatively under near-ultraviolet light, both the fifth intercostal nerve and its sensory branches auto-fluoresced clearly, so that surgery was completed without apparent injury to the fifth intercostal nerve or any of its branches. Postoperatively, the patient reported full sensory function throughout both breasts and both nipple–areolar complexes, which was confirmed on both tactile and thermal sensory testing at 3-month follow-up. The patient experienced no complications and rated her overall satisfaction with surgery on both breasts as 10 out of 10. To our knowledge, this is the first time sensory nerve auto-fluorescence has been reported to reduce the likelihood of intraoperative, iatrogenic nerve injury and preserve sensory function.